PENYIAPAN ALUMNI JURUSAN PENDIDIKAN BAHASA INGGRIS MENJADI WIRAUSAHAWAN KURSUS - Artini, Luh Putu; Padmadewi, Ni Nyoman; Nitiasih, P.K. (Universitas Negeri Yogyakarta, 2016)
This article reports the community service project on the implementation of a training model specially designed for alumni of English Education Department (hereafter, EED), Ganesha University of Education. The gradual increase of student body in EED has been found to have a direct effect on the longer waiting time for employment. It is common that they work as part time English instructors in private English courses while waiting for permanent employment. This kind of job has been considered temporal and it is unlikely to be taken seriously. Private English courses that provide general English tuitions are abundant, therefore, to be competitive the training follows a 100-hour English for Specific Purposes (hereafter, ESP) model. The materials involve 8 ESP packages that comprise English for Policeman, for Banking, for Hotel & Restaurant, Tour Guides, for Secretary, for Public Relation, and for Art shop attendants and Street Vendors. They also learn about course management and conducting fun classroom activities. All the trainers are experienced human resources in the fields. The project results in 8 material packages and strong motivation of the alumni to start entrepreneurship in ESP courses